Management of COPD exacerbations: a European Respiratory Society/American Thoracic Society guideline. Issue 3 (16th March 2017) - Wedzicha, Jadwiga A.; Miravitlles, Marc; Hurst, John R.; Calverley, Peter M.A.; Albert, Richard K.; Anzueto, Antonio; Criner, Gerard J.; Papi, Alberto; Rabe, Klaus F.; Rigau, David; Sliwinski, Pawel; Tonia, Thomy; et al.
This document provides clinical recommendations for treatment of chronic obstructive pulmonary disease (COPD) exacerbations. Comprehensive evidence syntheses, including meta-analyses, were performed to summarise all available evidence relevant to the Task Force's questions. The evidence was appraised using the Grading of Recommendations, Assessment, Development and Evaluation approach and the results were summarised in evidence profiles. The evidence syntheses were discussed and recommendations formulated by a multidisciplinary Task Force of COPD experts. After considering the balance of desirable and undesirable consequences, quality of evidence, feasibility, and acceptability of various interventions, the Task Force made: 1) a strong recommendation for noninvasive mechanical ventilation of patients with acute or acute-on-chronic respiratory failure; 2) conditional recommendations for oral corticosteroids in outpatients, oral rather than intravenous corticosteroids in hospitalised patients, antibiotic therapy, home-based management, and the initiation of pulmonary rehabilitation within 3 weeks after hospital discharge; and 3) a conditional recommendation against the initiation of pulmonary rehabilitation during hospitalisation. The Task Force provided recommendations related to corticosteroid therapy, antibiotic therapy, noninvasive mechanical ventilation, home-based management, and early pulmonary rehabilitation in patients having a COPD exacerbation. These recommendations should be reconsidered as new evidence becomes available. New guideline on the management of #COPD exacerbations from @ERStalk and @atscommunity http://ow.ly/Pvtr307YCMu